2020
DOI: 10.1177/1948550620934692
|View full text |Cite|
|
Sign up to set email alerts
|

A Bioweapon or a Hoax? The Link Between Distinct Conspiracy Beliefs About the Coronavirus Disease (COVID-19) Outbreak and Pandemic Behavior

Abstract: During the coronavirus disease pandemic rising in 2020, governments and nongovernmental organizations across the globe have taken great efforts to curb the infection rate by promoting or legally prescribing behavior that can reduce the spread of the virus. At the same time, this pandemic has given rise to speculations and conspiracy theories. Conspiracy worldviews have been connected to refusal to trust science, the biomedical model of disease, and legal means of political engagement in previous resea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
503
3
22

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 502 publications
(566 citation statements)
references
References 40 publications
38
503
3
22
Order By: Relevance
“…Nonetheless, we cannot rule out alternative explanations. Similarly, although we have modelled misinformation as a predictor of vaccine hesitancy consistent with prior work in this area [39,41,42], we note the likely possibility that causality can run both ways: being vaccine hesitant may, in turn, 14 We note that we cannot disentangle the causal direction of effects in this study. Both options are plausible, i.e., belief in COVID-19 misinformation could reduce willingness to get vaccinated, and prior vaccine hesitancy could increase belief in misinformation [73,74].…”
Section: Covid-19 Misinformation and Its Influence On Public Health Bmentioning
confidence: 54%
See 1 more Smart Citation
“…Nonetheless, we cannot rule out alternative explanations. Similarly, although we have modelled misinformation as a predictor of vaccine hesitancy consistent with prior work in this area [39,41,42], we note the likely possibility that causality can run both ways: being vaccine hesitant may, in turn, 14 We note that we cannot disentangle the causal direction of effects in this study. Both options are plausible, i.e., belief in COVID-19 misinformation could reduce willingness to get vaccinated, and prior vaccine hesitancy could increase belief in misinformation [73,74].…”
Section: Covid-19 Misinformation and Its Influence On Public Health Bmentioning
confidence: 54%
“…Aside from these more general predictors, recent research has evaluated public belief in and susceptibility to misinformation specifically about COVID-19 [27,[39][40][41][42]. A recent study by Uscinski et al [41] found that beliefs in conspiracies about the virus are associated with a propensity to reject information from expert authorities, raising concerns about the potential for popular conspiracy theories to reduce people's willingness to comply with public health guidance.…”
Section: Introductionmentioning
confidence: 99%
“…While it is true that similar forces tend to promote belief in conspiracy theories and misinformation (Enders & Smallpage, 2019), the specific content of each conspiracy theory and piece of misinformation is likely to attract its own set of adherents (Sternisko et al, 2020). The burgeoning literature on COVID-19 beliefs hints that there may be a structure to these dubious ideas, as they seem to vary in their content (Brennen et al, 2020), causal antecedents (Cassese et al, 2020;Uscinski et al, 2020), popularity (Miller, 2020), and behavioral and attitudinal consequences (Imhoff & Lamberty, 2020;Jolley & Paterson, 2020). However, researchers have yet to identify what the structure of COVID-19 conspiracy theories and misinformation looks like.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies find associations between belief in misinformation and reduced self-protective behaviors (Allington et al, 2020;Banai et al, 2020;Bertin et al, 2020;Bierwiaczonek et al, 2020;Erceg et al, 2020;Sternisko et al, 2020;Swami & Barron, 2020;Teovanovic et al, 2020), others find no evidence of associations (Alper et al, 2020;Díaz & Cova, 2020). Still others find associations for some behaviors but not others (Imhoff & Lamberty, 2020;Pummerer & Sassenberg, 2020). These inconsistent results may be driven by the varying quality, size, and representativeness of samples, by the validity of measures employed, or by the variety of assessed self-protective behaviors, ranging from social distancing and containment, to hygiene and hoarding tendencies, to future intentions to vaccinate.…”
Section: Past Studiesmentioning
confidence: 99%